Implantable and transdermal polymeric drug delivery technologies for the treatment of central nervous system disorders. (19th May 2017) - Govender, Thiresen; Choonara, Yahya E.; Kumar, Pradeep; Bijukumar, Divya; du Toit, Lisa C.; Modi, Girish; Naidoo, Dinesh; Pillay, Viness
Abstract: The complexity of the brain and the membranous blood–brain barrier (BBB) has proved to be a significant limitation to the systemic delivery of pharmaceuticals to the brain rendering them sub-therapeutic and ineffective in the treatment of neurological diseases. Apart from this, lack of innovation in product development to counteract the problem is also a major contributing factor to a poor therapeutic outcome. Various innovative strategies show potential in treating some of the neurological disorders; however, drug delivery remains the most popular. To attain therapeutic drug levels in the central nervous system, large, intolerable systemic doses are generally administered. The major factors responsible for the success maintenance therapy of neurological diseases included controlled and sustained release of neurotherapeutics, reduced frequency of administration, higher bioavailability, and patient compliances. Conventional oral or injectable formulations cannot satisfy all the requirements in many circumstances. This article reviews the therapeutic implantable polymeric and transdermal devices employed in an attempt to effectively achieve therapeutic quantities of drug across the BBB over a prolonged period, to improve patient disease prognosis.